Lithium Vanadyl Oxalatophosphite: Influence of the Water Content on the Crystal Structures and the Dehydration Scheme - Venegas-Yazigi, D; Venegas-Yazigi, D; Canon-Mancisidor, W; Canon-Mancisidor, W (2014)
Two new lithium vanadyl oxalatophosphites have been synthesized by hydrothermal treatment. The respective formula are Li2(VOHPO 3)2C2O4 6H2O (1) and Li2(VOHPO3)2C2O4 4H 2O (2). The structures of the compounds have been determined by single crystal X-ray diffraction. Compound 1 crystallizes in triclinic symmetry in space group P-1, a=6.3592(2) Å, b=8.0789(3) Å, c=9.1692(3) Å, ?=64.390(2), ?=87.277(2), ?=67.624(2) and, compound 2 in monoclinic symmetry, space group P21/a, a=6.3555(2) Å b=12.6368(7) Å c=9.0242(4) Å ?=105.167(3). The vanadium phosphite framework consists of infinite chains of corner-sharing vanadium octahedra and hydrogenophosphite tetrahedra. The oxalate groups ensure the connection between the chains. The lithium ions and the water molecules are located between the anionic [(VO)2(HPO3)2C 2O4]2- layers. Thermal behavior of both compounds was carefully studied by combining thermogravimetric analyses and thermal dependant X-ray diffraction in order to study the thermal stability of the layered oxalatophosphites and to see the influence of the decomposition of the carbon-based anions into the final lithium vanadyl phosphate. Various intermediate phases were evidenced and for both compounds the final product was LiVOPO4. © 2014 Elsevier Inc.